The Essential Skills for Becoming a Today's Automotive Vocational Teacher: Focus Group Interview Study - Yudantoko, Afri; Maruanaya, Rita Fransina; Gunadi, Gunadi (Universitas Negeri Yogyakarta, 2024)
Vocational education, as a kind of education, has an important role not only for people to get a job but also for nations to grow their national economy. Vocational teachers, especially, are the keys to the success of vocational education, so the competencies required to become such teachers are crucial issues that need attention. This study aims to explore the most needed and recent competencies that an automotive vocational teacher needs to master to survive in career life. A Focus Group Interview (FGI) study with two main questions was used to collect data from 6 participants consisting of 3 automotive vocational teachers and three automotive industrial instructors. The interview was recorded, and the data was analyzed qualitatively. The findings stated that the ability to conduct sustainable learning or lifelong learning becomes the most essential competency that automotive vocational teachers need to have. Additionally, there is a suggestion to automotive vocational teacher education institutions to conduct instructional design of learning activities that could promote the abilities of sustainable learning for the students. This is necessary because automotive technology is developing very quickly, so vocational education should deal with that phenomenon by preparing qualified automotive vocational teacher candidates who can conduct sustainable learning or lifelong learning effectively.